Religious sites and events as resources for tourism development in cities - case study: Novi Be?ej - Demirović, Dunja; Cimbaljević, Marija; Vujko, Aleksandra (Hotel and Tourism Management, 2018)
A large number of tourists are traveling motivated by the desire to learn about the historical and cultural heritage of cities which represent achievements in various fields of art. The volume of tourist traffic in cities depends on the wealth of cultural and historical monuments, environmental, events and other various contents which are concentrated in them. This paper analyzes all religious objects and events that are located in the municipality of Novi Be?ej (Serbia) and have importance for tourism development in order to create tourist values of these objects. 100 tourists were interviewed to determine the motives for visiting the municipality of Novi Be?ej and to assess the significance of religious objects and events for tourism development from demand side. Based on the survey results, a SWOT analysis was made in order to provide direction for the further development of tourism in the municipality of Novi Be?ej. Based on the evaluation of all the elements (tourist and geographical position, artistic value, ambiance, attractiveness, construction and fitting of tourism sites) and performed valuation, it was found that the municipality has a very good quality of cultural sites which distinguish the broader regional importance.